Stratified scaffolds for osteochondral tissue engineering applications: Electrospun PDLLA nanofibre coated Bioglass®-derived foams - Yunos, D. M.; Ahmad, Z.; Salih, V.; Boccaccini, Aldo R. (Journal of Biomaterials Applications, 2013)
This work focuses on designing bilayered constructs by combining electrospun poly-DL-Lactide (PDLLA) fibers and Bioglass®-derived scaffolds for development of osteochondral tissue replacement materials. Electrospinning was carried out using a solution of 5 wt/v% PDLLA in dimethyl carbonate. The PDLLA layer thickness increased from 2 to 150 μm with varying electrospinning time. Bioactivity studies in simulated body fluid showed that HA mineralization decreased as the thickness of the PDLLA layer increased. A preliminary in vitro study using chondrocyte cells (ATDC5) showed that cells attached, proliferated and migrated into the fibrous network, confirming the potential applicability of the bilayered scaffolds in osteochondral defect regeneration. © The Author(s) 2011 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.strati
Keywords: Bioactive glass; composites; osteochondral tissue engineering; scaffolds